Challenges In Managing HIV-Associated Co-Infection With Tuberculosis And Suspected Pneumocystis jirovecii pneumonia (PCP): A Case Report. - Sinaga, Fransisca T Y; Saputra, Tetra Arya; Choerunnisa, Nida (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2025)
HIV-positive individuals are highly vulnerable to opportunistic infections such as tuberculosis (TB) and Pneumocystis jirovecii pneumonia (PCP), particularly in low-resource, TB-endemic regions. We report a 30-year-old male patient with a history of unprotected multipartner sexual activity, diagnosed with clinical pulmonary TB and HIV infection, who developed progressive dyspnea, hypoxemia, and systemic symptoms over a four-month period. Physical examination revealed signs of pulmonary consolidation and neurologic abnormalities. Laboratory tests showed leukocytosis, hypoalbuminemia, and electrolyte imbalances. Imaging demonstrated bilateral lung infiltrates. The patient received antimicrobial therapy, electrolyte correction, and supportive care. Co-infection of TB and HIV with suspected PCP complicates diagnosis and necessitates an integrated approach. Clinicians must maintain high suspicion for overlapping infections in HIV-positive patients with deteriorating respiratory symptoms. Prompt clinical assessment, empiric therapy, and multidisciplinary management are essential in improving outcomes in resource-limited settings.